Christopher Hitchens the last interview and other conversations - Hitchens, Christopher 1949-2011 (Melville House, 2017)
"From Hitchens's earliest interviews to his final published interview with Richard Dawkins just before his death, this collection covers the brilliant career of Christopher Hitchens and tackles everything from atheism, his controversial support of the Iraq War, to America's march toward theocracy."...Provided by publisher
Keywords: Hitchens, Christopher -- Interviews; Hitchens, Christopher -- Political and social views; Hitchens, Christopher -- 1949-2011; Intellectuals -- United States -- Interviews; Journalists -- United States -- Interviews; Political activists -- United States -- Interviews; Authors, American -- Interviews; Interview; Biografie